Formylpeptide receptor 2: Nomenclature, structure, signalling and translational perspectives: IUPHAR review 35. (29th July 2022) - Qin, Cheng Xue; Norling, Lucy V.; Vecchio, Elizabeth A.; Brennan, Eoin P.; May, Lauren T.; Wootten, Denise; Godson, Catherine; Perretti, Mauro; Ritchie, Rebecca H.
Abstract : We discuss the fascinating pharmacology of formylpeptide receptor 2 (FPR2; often referred to as FPR2/ALX since it binds lipoxin A4 ). Initially identified as a low‐affinity 'relative' of FPR1, FPR2 presents complex and diverse biology. For instance, it is activated by several classes of agonists (from peptides to proteins and lipid mediators) and displays diverse expression patterns on myeloid cells as well as epithelial cells and endothelial cells, to name a few. Over the last decade, the pharmacology of FPR2 has progressed from being considered a weak chemotactic receptor to a master‐regulator of the resolution of inflammation, the second phase of the acute inflammatory response. We propose that exploitation of the biology of FPR2 offers innovative ways to rectify chronic inflammatory states and represents a viable avenue to develop novel therapies. Recent elucidation of FPR2 structure will facilitate development of the anti‐inflammatory and pro‐resolving drugs of next decade.